2023
DOI: 10.3389/fimmu.2022.1110516
|View full text |Cite
|
Sign up to set email alerts
|

Relative adrenal insufficiency is a risk factor and endotype of sepsis - A proof-of-concept study to support a precision medicine approach to guide glucocorticoid therapy for sepsis

Abstract: Introduction25-60% of septic patients experience relative adrenal insufficiency (RAI) and glucocorticoid (GC) is frequently used in septic patients. However, the efficacy of GC therapy and whether GC therapy should be based on the status of RAI are highly controversial. Our poor understanding about the pathogenesis of RAI and a lack of RAI animal model present significant barriers to address these critical issues.MethodsScavenger receptor BI (SR-BI) regulates stress-induced GC (iGC) production in response to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…SR-BI is a physiological HDL receptor and is well known for protecting against cardiovascular disease in both rodents and humans by mediating reverse cholesterol transportation in the liver (15). Our laboratory and others previously reported that SR-BI protects against polymicrobial sepsis (16)(17)(18) through multiple mechanisms, including mediating iGC production in the adrenal gland (17,(19)(20)(21). Thus, we hypothesized that SR-BI promotes iGC production in response to T cell activation in this noninfectious context by mediating the uptake of cholesteryl ester from HDL (Fig.…”
Section: T Cell Activation Induces the Adrenal Stress Response In Whi...mentioning
confidence: 95%
“…SR-BI is a physiological HDL receptor and is well known for protecting against cardiovascular disease in both rodents and humans by mediating reverse cholesterol transportation in the liver (15). Our laboratory and others previously reported that SR-BI protects against polymicrobial sepsis (16)(17)(18) through multiple mechanisms, including mediating iGC production in the adrenal gland (17,(19)(20)(21). Thus, we hypothesized that SR-BI promotes iGC production in response to T cell activation in this noninfectious context by mediating the uptake of cholesteryl ester from HDL (Fig.…”
Section: T Cell Activation Induces the Adrenal Stress Response In Whi...mentioning
confidence: 95%
“…25-60% of patients with sepsis experience relative adrenal insufficiency (RAI). Glucocorticoid treatment of mice with CLP-induced sepsis was found to be beneficial in RAI mice but detrimental in mice without RAI [ 47 ]. In the first phase 3 trial by Annane et al, low doses of hydrocortisone significantly reduced mortality in patients with septic shock and RAI [ 48 ].…”
Section: Introductionmentioning
confidence: 99%